Change of hematological blood indicators with acute combined intoxication with zinc, copper and arsenic salts - Tazitdinova, R.M.; Beisenova, R.R.; Fakhrudenova, I.B. (Fundamental and Experimental Biology, 2018)
This article indicated the investigation results on the morphofunctional blood changes of experimental animals with acute combined intoxication with heavy metal salts (zinc, copper, arsenic) carried out on 40 white outbred pubescent rats that were divided into four groups. It is noteworthy that heavy metals can accumulate in the animal and human organism. As the result, disturbed the functions of the different organs and systems and changed of hematological blood indicators. Biochemistry of blood can diagnose the pathology of the organism. There were used such solutions as copper sulfate, zinc sulphate and sodium arsenite as toxicants, which were intragastrically injected once. Blood sampling was conducted the next day after the injection. The results of our investigation showed that acute combined intoxication with zinc, copper and arsenic salts leads to the development of inflammatory processes in the body, which can be indicated by an increase of such blood indicators as leukocytes, erythrocytes, hemoglobin, hematocrit, mean hemoglobin in erythrocyte (MCH) and speed erythrocyte sedimentation (ESR). It was found that the combined effect of zinc and arsenic has the greatest toxic effect.